Building climate resilience of aquatic food production systems in Bangladesh - Hossain, Peerzadi; Barman, Benoy (WorldFish, 2024)
This factsheet explores how innovations in aquatic food systems in Bangladesh contribute to nature-positive climate adaptation and foster climate-resilient development in the face of climate change. It highlights interventions tailored to vulnerable regions, emphasizing sustainable solutions to enhance food security and climate adaptation.